Misunderstanding in intercultural electronic written communication in Chinese business field - Guo, Xiaoxi (Walter de Gruyter GmbH, 2023)
The prevalence of intercultural communication in the business domain has led to an increase in the occurrence of misunderstandings. The advancement of telecommunication technology and the implementation of epidemic prevention policies in various countries have resulted in electronic written communication becoming the most widely utilized method for business interactions, thereby giving rise to a significant number of misunderstandings. Hence, it is imperative to investigate the specific reasons for misunderstandings within a particular country. Given China's prominent global position, it is crucial to conduct a thorough examination of Chinese companies and workers. Thus, this article aims to identify the sources and strategies employed to address misunderstandings in intercultural electronic written communication in China by analyzing naturally occurring electronic written communication documents and conducting interviews with Chinese businesspersons. The findings reveal that language-related and culture-related factors are the primary causes of misunderstandings. Chinese businesspersons have employed strategies such as seeking advice from familiar Chinese coworkers, engaging in further communication with the interlocutors, and modifying their own expression habits to resolve and prevent misunderstandings. Researching the distinctive forms and causes of misunderstandings in electronic written communication is essential for individuals engaged in international business to identify solutions and enhance communication efficiency by minimizing misunderstandings.